1999
DOI: 10.4141/s98-028
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate application and timing of tillage of red clover affects potato response to N, soil N profile, and root and soil nematodes

Abstract: , J. 1999. Glyphosate application and timing of tillage of red clover affects potato response to N, soil N profile, and root and soil nematodes. Can J. Soil Sci. 79: 65-72. The effects of glyphosate application and time of tillage of red clover on soil NO 3 -N profiles, the response of the subsequent potato crop to varying rates of N fertilizer application, and root and soil nematodes, were evaluated. The study was conducted over three cropping seasons on a Charlottetown fine sandy loam on Prince Edward Island… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 13 publications
3
31
0
2
Order By: Relevance
“…Furthermore, the relatively high N content of the red clover would probably encourage rapid mineralization and decomposition of the red clover mulch, compared with mulch from grain crops (e.g., Neeteson 1989;Sanderson et al 1999).…”
Section: Surface Residue Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the relatively high N content of the red clover would probably encourage rapid mineralization and decomposition of the red clover mulch, compared with mulch from grain crops (e.g., Neeteson 1989;Sanderson et al 1999).…”
Section: Surface Residue Levelsmentioning
confidence: 99%
“…Neeteson (1989) showed that the addition of red clover in a 4-yr potato rotation, on a heavy loam soil in The Netherlands, could lower the fertilizer N requirement in the potato year, although nitrate-N leaching in the winter period after clover growth was a concern. On sandy loam soils in Prince Edward Island, Sanderson et al (1999) compared time of mouldboard and chisel plough autumn tillage of red clover with the soil nitrate-N profiles under the following potato crop. Compared with a barley control, inclusion of red clover prior to potato provided a substantial N source for the subsequent potato crop and also influenced soil nitrate-N profiles.…”
Section: Was 44 Mg Hamentioning
confidence: 99%
“…The relationship between Nop and spring soil NO 3 -N did not change significantly when we consider the data with forages as a previous crop separately (Fig.1, Table 2). This is not surprising because the time of fall ploughing of forages can substantially affect the quantity of mineralized soil N in the spring (Sanderson et al 1999). In our field experiment, the timing of fall ploughing was not controlled but determined by individual landowners at all sites.…”
Section: Soil No 3 -N Contents In Spring and Mid-seasonmentioning
confidence: 99%
“…For example, crop yield response to increasing rates of fertilizer N application (Sanderson et al 1999;Bélanger et al 2000) provides an estimate of the optimal fertilizer N rate, and can be used to estimate the relative magnitude of soil N supply. Similarly, plant-based tests can be used to assess crop N sufficiency (Porter and Sisson 1991a;Minotti et al 1994).…”
mentioning
confidence: 99%